diff --git a/FLT3/FLT3.lean b/FLT3/FLT3.lean index 59904f9..8e231ef 100644 --- a/FLT3/FLT3.lean +++ b/FLT3/FLT3.lean @@ -960,8 +960,7 @@ lemma by_kummer : ā†‘S.uā‚„ āˆˆ ({1, -1} : Finset (š“ž K)) := by Ā· use -1 use kX - kY - S.uā‚„ * kZ rw [show Ī» ^ 2 * (kX - kY - ā†‘(uā‚„ S) * kZ) = Ī» ^ 2 * kX - Ī» ^ 2 * kY - ā†‘(uā‚„ S) * (Ī» ^ 2 * kZ) by ring] - rw [ā† hkX, ā† hkY, ā† hkZ] - rw [ā† S.formula2] + rw [ā† hkX, ā† hkY, ā† hkZ, ā† S.formula2] ring Ā· use 1 use - kX + kY + S.uā‚„ * kZ diff --git a/blueprint/src/chapters/2-case2.tex b/blueprint/src/chapters/2-case2.tex index 6d9a2cc..574af77 100644 --- a/blueprint/src/chapters/2-case2.tex +++ b/blueprint/src/chapters/2-case2.tex @@ -1158,8 +1158,36 @@ \chapter{Case 2} \uses{lmm:lambda_sq_div_lambda_fourth, lmm:lambda_sq_div_new_X_cubed, lmm:eq_one_or_neg_one_of_unit_of_congruent, lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd, - lmm:lambda_not_dvd_Z, lmm:formula2} - % TODO + lmm:lambda_not_dvd_Z, lmm:lambda_not_dvd_Y, lmm:formula2} + Let $n \in \N$ be the multiplicity of the solution $S$.\\ + By \Cref{lmm:eq_one_or_neg_one_of_unit_of_congruent}, it suffices to prove that + $$\exists m \in \Z \text{ such that } \lambda^2 \divides u_4 - m.$$ + By \Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd} + and \Cref{lmm:lambda_not_dvd_Y}, we have that + $$(\lambda^4 \divides Y^3 - 1) \lor (\lambda^4 \divides Y^3 + 1).$$ + By \Cref{lmm:lambda_pow_four_dvd_cube_sub_one_or_add_one_of_lambda_not_dvd} + and \Cref{lmm:lambda_not_dvd_Z}, we have that + $$(\lambda^4 \divides Z^3 - 1) \lor (\lambda^4 \divides Z^3 + 1).$$ + We proceed by analysing each case: + \begin{itemize} + \item Case $(\lambda^4 \divides Y^3 - 1) \land (\lambda^4 \divides Z^3 - 1)$. \\ + Let $m=-1$ and consider the fact that + $$u_4 - m = Y^3 + u_4 Z^3 - (Y^3 - 1) - u_4 (Z^3 - 1).$$ + By \Cref{lmm:formula2}, we have that + $$u_4 - m = u_5 (Ī»^{n-1} X)^3 - (Y^3 - 1) - u_4 (Z^3 - 1).$$ + Since, by \Cref{lambda_sq_div_new_X_cubed}, we know that + $$\lambda^2 \divides u_5 (Ī»^{n-1} X)^3$$ + and, by \Cref{lmm:lambda_sq_div_lambda_fourth} and by assumption, we have that + $$\lambda^2 \divides Y^3 - 1 \land \lambda^2 \divides Z^3 - 1,$$ + Then, we can conclude that + $$\lambda^2 \divides u_4 - m.$$ + \item Case $(\lambda^4 \divides Y^3 - 1) \land (\lambda^4 \divides Z^3 + 1)$. \\ + Let $m=1$ and proceed similarly to the first case. + \item Case $(\lambda^4 \divides Y^3 + 1) \land (\lambda^4 \divides Z^3 - 1)$. \\ + Let $m=1$ and proceed similarly to the first case. + \item Case $(\lambda^4 \divides Y^3 + 1) \land (\lambda^4 \divides Z^3 + 1)$. \\ + Let $m=-1$ and proceed similarly to the first case. + \end{itemize} \end{proof} \begin{lemma}